Implementation of a Health Management Mentoring Program: Year-1 Evaluation of Its Impact on Health System Strengthening in Zambézia Province, Mozambique - Laura J. Edwards; Abú Moisés; Mathias Nzaramba; Aboobacar Cassimo; Laura Silva; Joaquim Mauricio; C. William Wester; Sten H. Vermund; Troy D. Moon (Kerman University of Medical Sciences, 2015)
Background Avante Zambéziais an initiative of a Non-Governmental Organization (NGO), Friends in Global Health, LLC (FGH) and the Vanderbilt Institute for Global Health (VIGH) to provide technical assistance to the Mozambican Ministry of Health (MoH) in rural Zambézia Province. Avante Zambézia developed a district level Health Management Mentorship (HMM) program to strengthen health systems in ten of Zambézia's 17 districts. Our objective was to preliminarily analyze changes in four domains of health system capacity after the HMM's first year: accounting, Human Resources (HRs), Monitoring and Evaluation (M&E), and transportation management. Methods Quantitative metrics were developed in each domain. During district visits for weeklong, on-site mentoring, the health management mentoring teams documented each indicator as a success ratio percentage. We analyzed data using linear regressions of each indicator's mean success ratio across all districts submitting a report over time. Results Of the four domains, district performance in the accounting domain was the strongest and most sustained. Linear regressions of mean monthly compliance for HR objectives indicated improvement in three of six mean success ratios. The M&E capacity domain showed the least overall improvement. The one indicator analyzed for transportation management suggested progress. Conclusion Our outcome evaluation demonstrates improvement in health system performance during a HMM initiative. Evaluating which elements of our mentoring program are succeeding in strengthening district level health systems is vital in preparing to transition fiscal and managerial responsibility to local authorities.